Association between sleep quality and benign prostate hyperplasia among middle-aged and older men in India - Kai Ma; Qiang Dong (BMC, 2023)
Abstract Background The association between sleep quality and benign prostate hyperplasia (BPH) has rarely been studied. The aim of this study was to examine the relationship between sleep quality and BPH among middle-aged and older men in India. Methods This study used data from men over 45 years old in Wave 1 (2017-2018) of the Longitudinal Aging Study in India (LASI). Benign prostate hyperplasia was self-reported, and sleep symptoms were assessed using five questions modified from the Jenkins Sleep Scale. A total of 30,909 male participants were finally included. Multivariate logistic regression analysis, subgroup analysis, and interaction tests were performed. Results Total 453 (1.49%) men reported benign prostatic hyperplasia and have higher sleep quality score (9.25 ± 3.89 vs. 8.13 ± 3.46). The results revealed that the sleep quality score and risk of benign prostatic hyperplasia were significantly correlated after adjusting for all confounding factors (OR:1.057, 95% CI: 1.031-1.084, p < 0.001]. After dividing people into four groups based on the quartile of sleep quality scores, compared with the first quartile group, the third quartile group was 1.32 times, and the fourth quartile group was 1.615 times more likely to develop benign prostate hyperplasia. A significant interaction effect of alcohol consumption was observed. (p for interaction < 0.05). Conclusion Worse sleep quality was significantly associated with a higher incidence of benign prostatic hyperplasia among middle-aged and older Indian men. A further prospective study is needed to clarify this association and explore potential mechanisms.